Influence of 68Ga-DOTATOC on sparing of normal tissue for radiation therapy of skull base meningioma: Differential impact of photon and proton radiotherapy - Stade, Falk; Dittmar, Jan-Oliver; Jaekel, Oliver; Kratochwil, Clemens; Haberkorn, Uwe; Debus, Juergen; Combs, Stephanie E. (Radiation Oncology, 2018)
Background: To evaluate the impact of 68Ga-DOTATOC-PET on treatment planning and sparing of normal tissue in the treatment of skull base meningioma with advanced photons and protons. Methods: From the institutional database consisting of 507 skull base meningiomas 10 patients were chosen randomly for the present analysis. Target volume definition was performed based on CT and MRI only, as well as with additional 68Ga-DOTATOC-PET. Treatment plans were performed for Intensity Modulated Radiotherapy (IMRT) and proton therapy using active raster scanning on both target volumes. We calculated doses to relevant organs at risk (OAR), conformity indices as well as differences in normal tissue sparing between both radiation modalities based on CT/MRI planning as well as CT/MRI/PET planning. Results: For photon treatment plans, PET-based treatment plans showed a reduction of brain stem Dmax and Dmedian for different levels of total dose. At the optic chiasm, use of 68Ga-DOTATOC significantly reduces Dmax; moreover, the Dmedian is reduced in most cases, too. For both right and left optic nerve, reduction of dose by addition of 68Ga-DOTATOC-PET is minimal and depends on the anatomical location of the meningioma. In protons, the impact of 68Ga-DOTATOC-PET is minimal compared to photons. Conclusion: Addition of 68Ga-DOTATOC-PET information into treatment planning for skull base meningiomas has a significant impact on target volumes. In most cases, PET-planning leads to significant reductions of the treatment volumes. Subsequently, reduced doses are applied to OAR. Using protons, the benefit of additional PET is smaller since target coverage is more conformal and dose to OAR is already reduced compared to photons. Therefore, PET-imaging has the greatest margin of benefit in advanced photon techniques, and combination of PET-planning and high-precision treatment leads to comparable treatment plans as with protons.
CRIS-Team Scopus Importer:2023-03-08
Keywords: IMRT; OAR; Proton therapy; Skull base meningioma